2017
DOI: 10.1002/2017je005434
|View full text |Cite
|
Sign up to set email alerts
|

Recent Basal Melting of a Mid‐Latitude Glacier on Mars

Abstract: Evidence for past basal melting of young (late Amazonian‐aged), debris‐covered glaciers in Mars' mid‐latitudes is extremely rare. Thus, it is widely thought that these viscous flow features (VFFs) have been perennially frozen to their beds. We identify an instance of recent, localized wet‐based mid‐latitude glaciation, evidenced by a candidate esker emerging from a VFF in a tectonic rift in Tempe Terra. Eskers are sedimentary ridges deposited in ice‐walled meltwater conduits and are indicative of glacial melti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 112 publications
2
46
1
Order By: Relevance
“…On Earth, high geothermal heat fluxes of >200 mW/m 2 have been observed beneath the Antarctic ice sheet (Fisher et al, 2015;Schroeder et al, 2014), much greater than the average terrestrial value. Models of Martian midlatitude glaciation similarly found that increases in geothermal heat flux were needed to achieve subglacial melting but also required strain heating of the ice due to internal deformation of flowing ice (Butcher et al, 2017). However, most of these factors are either already accounted for in the models that predict Mars' low geothermal heat flux (such as crustal thickness) or are not applicable to Mars (such as factors related to plate tectonics).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On Earth, high geothermal heat fluxes of >200 mW/m 2 have been observed beneath the Antarctic ice sheet (Fisher et al, 2015;Schroeder et al, 2014), much greater than the average terrestrial value. Models of Martian midlatitude glaciation similarly found that increases in geothermal heat flux were needed to achieve subglacial melting but also required strain heating of the ice due to internal deformation of flowing ice (Butcher et al, 2017). However, most of these factors are either already accounted for in the models that predict Mars' low geothermal heat flux (such as crustal thickness) or are not applicable to Mars (such as factors related to plate tectonics).…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these factors are either already accounted for in the models that predict Mars' low geothermal heat flux (such as crustal thickness) or are not applicable to Mars (such as factors related to plate tectonics). Models of Martian midlatitude glaciation similarly found that increases in geothermal heat flux were needed to achieve subglacial melting but also required strain heating of the ice due to internal deformation of flowing ice (Butcher et al, 2017). This effect is not observed to be occurring in the polar layered deposits (Karlsson et al, 2011), nor is it predicted to occur except possibly at some margins (Sori et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The VFFs are believed to behave like cold-based glaciers on Earth, where the ice is frozen to the bed and the flow is dominated by deformation of mass above by gravity-driven viscous creep (Mangold and Allemand, 2001;Pierce and Crown, 2003;Li et al, 2005;Karlsson et al, 2015). Only in two locations have eskers been linked to VFF, providing evidence of basal glacial melting (Gallagher and Balme, 2015;Butcher et al, 2017). Rare supraglacial valleys have been attributed to transient supraglacial melting encouraged by focussing of solar radiation onto VFF surfaces from steep adjacent topography (Fassett et al, 2010).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The planform geometry of these ridges is strong evidence that they are depositional channel systems now preserved as inverted relief (inverted fluvial channels; Burr et al, ; Davis et al, ; Pain et al, ; Williams et al, ). These ridges are interpreted as inverted fluvial channels rather than glacial eskers as they conform to regional topography (i.e., they do not go upslope) and lack associated glacier landforms commonly found with eskers (e.g., Butcher et al, ; Gallagher & Balme, ). Alternatively, the ridges may be the eroded remnants of erosional valley walls; however, given that multiple tributary ridges converge in the downslope direction, they are more consistent with inverted channels.…”
Section: Observationsmentioning
confidence: 99%